The impact on biodiversity, and integrated control, of water hyacinth, Eichhornia crassipes (Martius) Solms-Laubach (Pontederiaceae) on the Lake Nsezi - Nseleni River system - Jones, Roy William (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
Water hyacinth, Eichhornia crassipes (Martius) Solms-Laubach (Pontederiaceae), a free floating aquatic plant was discovered by C. von Martius in 1823 in Brazil. It is believed to have been introduced into South Africa, as an ornamental plant, in 1908 to the Cape Province and Natal. Since its introduction, water hyacinth has spread throughout South Africa to the detriment of all aquatic systems that it has been introduced to directly or indirectly. The weed was first positively identified on the Nseleni and Mposa rivers on the Nseleni Nature Reserve which is a protected area near Richards Bay in KwaZulu- Natal in 1982 and formed a 100% cover of the river by 1983. An integrated management plan was implemented in 1995 and resulted in a reduction of the weed from a 100% cover to less than 20% cover in 5 years. The keys to success of the water hyacinth integrated management plan, presented here, were finding the source of the weed, mapping the extent of the water hyacinth infestation, identifying sources of nutrient pollution, appointing a champion to drive the programme, dividing the river into management units, consultation with interested and affected parties, judicious use of herbicides and biological control and a commitment to follow-up. This study further showed that water hyacinth on the Nseleni and Mposa river systems had a negative impact on the biodiversity of the protected area and the control of water hyacinth resulted in the recovery of the benthic invertebrate, amphibian, reptile, fish and avian fauna. The implementation of this integrated management plan was very cost-effective and serves as a model approach to the control of water hyacinth in both South Africa and the rest of the world.
Keywords: Water hyacinth -- Control -- South Africa; Eichhornia crassipedes; Pontederiaceae; Aquatic plants -- South Africa -- Nsezi, Lake; Aquatic weeds -- South Africa -- Nsezi, Lake; Invasive plants -- South Africa -- Nsezi, Lake